2000
DOI: 10.1161/01.atv.20.4.1137
|View full text |Cite
|
Sign up to set email alerts
|

Major Reduction in Plasma Lp(a) Levels During Sepsis and Burns

Abstract: Abstract-Plasma levels of lipoprotein(a) [Lp(a)], an atherogenic particle, vary widely between individuals and are highly genetically determined. Whether Lp(a) is a positive acute-phase reactant is debated. The present study was designed to evaluate the impact of major inflammatory responses on plasma Lp(a) levels. Plasma levels of C-reactive protein (CRP), low density lipoprotein cholesterol, Lp(a), and apolipoprotein(a) [apo(a)] fragments, as well as urinary apo(a), were measured serially in 9 patients admit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 52 publications
4
35
0
Order By: Relevance
“…37 This suggests that, at least in the samples examined, the elastolytic activity in synovial fluid was sufficiently inhibited by anti-proteases and/or that apo(a) is rather insensitive, in vivo, to digestion. As such, the present data are in line with our previous observation, in which we showed that no apo(a) fragments were generated in the circulation during cardiopulmonary bypass 38 or sepsis, 32 two conditions characterized by marked release of elastase by polymorphonuclear cells.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…37 This suggests that, at least in the samples examined, the elastolytic activity in synovial fluid was sufficiently inhibited by anti-proteases and/or that apo(a) is rather insensitive, in vivo, to digestion. As such, the present data are in line with our previous observation, in which we showed that no apo(a) fragments were generated in the circulation during cardiopulmonary bypass 38 or sepsis, 32 two conditions characterized by marked release of elastase by polymorphonuclear cells.…”
Section: Discussionsupporting
confidence: 93%
“…Apo(a) was quantitated by a sandwich enzyme-linked immunosorbent assay using mouse anti-apo(a) monoclonal antibodies of well-defined specificity, 31 as described. 32 small fraction (ϳ2%) of apo(a) immunoreactive material, were hardly visible on this exposure (lanes 2 and 8). The size of apo(a) in untreated synovial fluid (lanes 4 and 10) was similar to the one of full-length apo(a) in plasma.…”
Section: Apo(a) In Human Synovial Fluid Corresponds To Full-length Apmentioning
confidence: 94%
See 2 more Smart Citations
“…Some studies showed that levels of Lp[a] are increased during stress (120,121), whereas others reported no changes or a reduction (122,123). These conflicting data may be attributable to the specificity of the assays used to measure Lp[a] levels or to interindividual variation in plasma Lp[a] levels in the population.…”
Section: Cholesterol Metabolismmentioning
confidence: 99%